Stephen Fry’s “Mythos” – A Modern Adaptation of Ancient Greek Myths and Legends - Statulova, Daniela (Media and Language, 2025)
The text deals with Stephen Fry’s Mythos as a modern, authentic and humorous adaptation of the ancient Greek mythology. The study focuses on the applied language policies and practices, as well as the achieved balance in the language situations and formations. The creative figure of the author with a special point of view of the modern world and accepted stereotypes are essential. The research methodology combines theoretical and interdisciplinary analyses.